Att bli kunglig: Kunglighet och folklighet i Svensk Damtidning - Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2009)
In 2002 it became known to the public that the crown princess of Sweden had a new boyfriend. A native from Ockelbo, a small community in the county of Gästrikland, Daniel was soon described as "a man of the people" and class-difference was made the prime topic of much media-coverage. Was Daniel worthy? Would he be accepted by the king? Would he be able to learn to behave as part of the royal family? This article aims at describing and analysing the way the category of "the peopl" was used and reproduced in the articles and notices in Svensk Damtidning, on of Sweden's largest women's magazines describing itself as the royal weekly. Using concepts of postmarxist discourse theory as it has been developed by Ernesto Laclau and Chantal Mouffe, the article shows how the categories of "people" and "royalty" were constructed in relation to characteristics of normative ideas of gender and taste, but also of hard working entrepreneurial spirit and everydayness.